A Window on the Lung: Molecular Imaging as a Tool to Dissect Pathophysiologic Mechanisms of Acute Lung Disease. (25th August 2019) - Musch, Guido
Abstract : In recent years, imaging has given a fundamental contribution to our understanding of the pathophysiology of acute lung diseases. Several methods have been developed based on computed tomography (CT), positron emission tomography (PET), and magnetic resonance (MR) imaging that allow regional, in vivo measurement of variables such as lung strain, alveolar size, metabolic activity of inflammatory cells, ventilation, and perfusion. Because several of these methods are noninvasive, they can be successfully translated from animal models to patients. The aim of this paper is to review the advances in knowledge that have been accrued with these imaging modalities on the pathophysiology of acute respiratory distress syndrome (ARDS), ventilator-induced lung injury (VILI), asthma and chronic obstructive pulmonary disease (COPD).